Effect of Ashitaba Extract on Cholesterol in Wistar Rats Given a High-Fat Diet and Computational Lethal Dose Test - Widyaningsih, Indah; Nurulita Sugiharto, Natasya; Rahmawati, Febtarini; Amma, Fuad; Simamora, Dorta (Syntax Corporation Indonesia, 2024)
High cholesterol levels in the blood can cause various health problems, namely atherosclerosis, stroke, coronary heart disease, and hypertension. One drug option for someone with hypercholesterolemia is simvastatin. Apart from using simvastatin, you can consume medicinal plants. A medicinal plant that can help reduce high cholesterol levels is Ashitaba (Angelica keiskei) leaf extract. One of the ingredients in Ashitaba extract is xanthoangelol E, Ashitaba chalcones, which can reduce cholesterol synthesis. The aim of this research was to determine the effect of ashitaba (Angelica keiskei) extract on the cholesterol levels of Wistar rats (Rattus novergiccus) given a high-fat diet. In this study, a computational lethal dose test was also carried out. The population in this study was male white rats of the Wistar strain with 30 samples taken. Analysis of this research data uses the One Way Anova statistical test. The results of the study showed that giving ashitaba extract 150mg/kg BW, 300mg/kg BW, and 600mg/kg BW had no effect on the cholesterol levels of Wistar rats given a high-fat diet. This is proven by the results of the Anova test which obtained a significance value of 0.761 > 0.05. Research regarding the toxic effects of ashitaba extract needs to be carried out for further research.